The strength of a people : the idea of an informed citizenry in America, 1650-1870 - Brown, Richard D. (Chapel Hill, N.C. : University of North Carolina Press, 1996)
Thomas Jefferson's conviction that the health of the nation's democracy would depend on the existence of an informed citizenry has been a cornerstone of our political culture since the inception of the American republic. Even today's debates over education reform and the need to be competitive in a technologically advanced, global economy are rooted in the idea that the education of rising generations is crucial to the nation's future. In this book, Richard Brown traces the development of the ideal of an informed citizenry in the seventeenth through nineteenth centuries and assesses its continuing influence and changing meaning.
Ch. 1. English Subjects and Citizens from the Reformation through the Glorious Revolution -- Ch. 2. Freedom and Citizenship in Britain and Its American Colonies -- Ch. 3. Bulwark of Revolutionary Liberty: The Recognition of the Informed Citizen -- Ch. 4. Shaping an Informed Citizenry for a Republican Future -- Ch. 5. The Idea of an Informed Citizenry and the Mobilization of Institutions, 1820-1850 -- Ch. 6. Testing the Meaning of an Informed Citizenry, 1820-1870 -- Epilogue: Looking Backward: The Idea of an Informed Citizenry at the End of the Twentieth Century.
Includes bibliographical references (pages 209-243) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Political science -- United States -- History; Political socialization -- United States -- History; Freedom of information -- United States -- History; Civics -- Study and teaching -- United States -- History; Socialisation politique -- États-Unis -- Histoire; Liberté d'information -- États-Unis -- Histoire; Éducation à la citoyenneté -- États-Unis -- Histoire; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; Civics -- Study and teaching; Freedom of information; Political science; Political socialization; United States; Burgerschap; Vorming; Political science -- United States -- History; Political socialization -- United States -- History; Freedom of information -- United States -- History; Civics -- Study and teaching -- United States -- History; History